Dampak Kebijakan BI Rate Repo 7 Days terhadap Kinerja Bank Pemerintah - Sofyan Marwansyah; Sri Rusiyati (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2019)
The policy to overcome the inflation lane is usually the central bank uses an interest rate policy called the BI Rate, but the BI Rate policy is deemed ineffective for banks because it requires a long time to a year, so the central bank issues a 7-day BI Rate Repo with the aim to effective in carrying out financial system policies. The purpose of this writing is first; to determine the influence of BI Rate Repo policy on Capital Ratios and Profitability ratios of Government banks, second; to see if there are significant differences in capital performance and profitability of government banks due to the 7 Days BI Rate repo policy. The research results obtained that the BI Rate has a negative significant relationship to the capital ratio (CAR) while the profitability ratio (ROE) has a positive significant relationship; The BI Rate affects the Capital Ratio (CAR) of 27.6% while the Profitability Ratio is 17.2%; The Capital Ratio Rate (CAR) has a significant difference between before the BI Rate Repo policy and after the policy which has increased from 18.65 to 20.42; The profitability ratio (ROE) has a significant difference between before the BI Rate Repo policy and after the policy, which decreased from 20.24 to 16.59.